An Exploratory Investigation of Teacher Perceptions of Education and Communication at the Beginning of the COVID-19 Pandemic - Stephenson J. Beck; Emily A. Paskewitz (Central States Communication Association, 2022)
In March 2020, teachers in the K-12 school system were forced to transition from in-person instruction to a variety of virtual teaching models due to the COVID-19 pandemic. This unprecedented change required extensive communication between teachers, students, parents, and administrators. This study explored communication during the March-May 2020 transition period, utilizing Uncertainty Management Theory as an overarching framework to investigate how teacher comfort with online learning, communication overload, administrative clarity, and student-teacher interaction influenced the effectiveness and happiness of teachers. Across these four variables, communication overload was shown to be a strong negative predictor of teacher well-being; student-teacher interaction predicted positive teaching outcomes.